Covid-19 and Violence Againts Women: an Islamic Perspective - Noor Hidayah (Cakrawala: Jurnal Studi Islam, 2020)
The increasing cases of COVID-19 have affected the rapid cases of violence against women in the world. Furthermore, this massive violence has raised a lot of concern in many circles. By using a literature approach that explores the various reading material such as journal articles, books, reports, news, and statistical data, this study is qualitative descriptive research that discusses on what is the position of women during pandemic COVID-19. In addition, this article also examines the issues and the background that drives the increasing violence cases on women in the shadow COVID-19 together with an Islamic analysis on it. The primary finding of this study is the position and the condition of women in the pandemic COVID-19 is still neglected. Hence, women are increasingly facing the risk of violence whatever they are in and based on the Islamic perspective these cases can mitigate by cultivating social care.